Demosthenes of Athens and the fall of classical Greece - Worthington, Ian (Oxford University Press, 2013)
Demosthenes (384-322 BC) profoundly shaped one of the most eventful epochs in antiquity. His political career spanned three decades, during which time Greece fell victim to Macedonian control, first under Philip II and then Alexander the Great. Demosthenes' courageous defiance of Macedonian imperialism cost him his life but earned him a reputation as one of history's outstanding patriots. He also enjoyed a brilliant and lucrative career as a speechwriter, and his rhetorical skills are still emulated today by statesmen and politicians. Yet he was a sickly child with a challenging speech impediment, who was swindled out of much of his family's estate by unscrupulous guardians.